Дунд масштабын геоморфологийн зураг боловсруулах аргазүйн асуудалд - Б, Баянжаргал; М, Нямхүү (Proceedings of the Mongolian Academy of Sciences, 2017)
In order to classify morphology and morphogenetic features of Mongolian eastern region, it is based on the field study measurements, high accurate digital elevation model (DEM), large scale topographical map and targeted to use mapping methodology on chosen territory. We have used geomorphological mapping traditional method and modern advanced technology for this study. As a result, we have received more precise results. According to describing of Mechislav Klimaschewski: Geomorphological map must include appearance, size, origin, age, location of morphology, some information of boundaries between them, also morphometry, morphography, morphogenetic and morph chronical information. As a result of this study, we have mapped geomorphological map based on principle of morphogenetic. This map is consists of 4 groups, 12 features, 58 sub features of origin, and map legends are imaged by map symbols and different colors. Depending on map scale, some morphological features which are impossible to denote are denoted by point and line symbols.